Relationship Of Financial Leverage On Investment Decisions And Firms' Value: Evidence From Indonesia Manufacturing Companies - Misrah, Misrah; Arifin, Arifin (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze and empirically test the impact of financial leverage on investment decisions, firms' value, and the role of investment decisions as a mediator. This study uses a quantitative approach with secondary data. Manufacturing companies listed on the Indonesia Stock Exchange in 2016-2022 are the research population. Sampling was done using purposive sampling, and a sample of 117 companies was obtained. The data analysis technique used structural equation modeling. The study's results showed that leverage did not affect investment decisions. However, leverage showed a positive effect on firms' value. Investment decisions have a positive effect on firms' value. Investment decisions can mediate the effect of leverage on firms' value. This study theoretically offers a framework for understanding the role of financial leverage on firm value through investment decisions. In addition, this study can be a reference for further research. Practically, this study can be a reference for investors in choosing stock investments and stakeholders in manufacturing companies to overcome obstacles, maximize market value, and optimize capital structure.